2002
DOI: 10.1590/s0100-879x2002000100013
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the test situation on pup retrieval behavior of normal and undernourished lactating rats

Abstract: Undernutrition of dams and pups disrupts the retrieval efficiency of mothers. However, if the mothers are assessed in their home cages, they spend more time with their litters. In the present study the effect of test conditions on pup retrieval behavior of mothers receiving a 25% (well-nourished group) and 8% casein diet (undernourished group) was examined. In agreement with previous studies, undernourished mothers spent more time with their litters than well-nourished dams as lactation proceeded. Pup retrieva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 29 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…Pup retrieval behaviour, including success at retrieving the entire litter within the experimental period and latency to retrieve pups, was not significantly affected by group, F 0 diet, or F 1 exposure, although dams in the HF -hf group showed a non-significant impairment in retrieval compared to other groups. Other studies have suggested a link between diet and pup retrieval behaviours, but this is context-and age-dependent [18,29]. For example, in one study, dams on a HF diet demonstrated impaired pup retrieval on postnatal day 7 but not on postnatal day 4 [18], with the latter time point being close to our own study.…”
Section: Discussionsupporting
confidence: 84%
“…Pup retrieval behaviour, including success at retrieving the entire litter within the experimental period and latency to retrieve pups, was not significantly affected by group, F 0 diet, or F 1 exposure, although dams in the HF -hf group showed a non-significant impairment in retrieval compared to other groups. Other studies have suggested a link between diet and pup retrieval behaviours, but this is context-and age-dependent [18,29]. For example, in one study, dams on a HF diet demonstrated impaired pup retrieval on postnatal day 7 but not on postnatal day 4 [18], with the latter time point being close to our own study.…”
Section: Discussionsupporting
confidence: 84%
“…nest lining that was higher in restricted than ad libitum fed rabbits. In rats, Rocha et al (2002) concluded that pup retrieval behaviour of the undernourished mother was not impaired by dietary restriction.…”
Section: Reproductive Performancementioning
confidence: 99%
“…in order to facilitate nursing, dams adopt a nursing posture, arching the back and covering the pups, while licking them to keep their bodies clean and stimulate metabolism. until postnatal day 14, separating the pups from the dam leads the dam to repeatedly retrieve them into the nest [5,8,31], and this behavior is frequently used to evaluate parenting ability.…”
Section: Evaluation Of Maternal Behaviormentioning
confidence: 99%